Políticas Educativas, Avaliação e Trabalho Docente: o caso de um programa de intervenção pedagógica no Rio Grande do Sul. - Souza, Fernanda Amaral de (2011)
The research analyses how the Alfa and Beto Reading and Writing Pedagogical Intervention Program (Programa de Intervenção Pedagógica de Alfabetização Alfa e Beto), a private funded initiative, was institutionalized in two public schools in the state of Rio Grande do Sul (RS, Brazil), in the 2007-2010 administration; and how teachers perceive their work in order to understand what effects it may have over autonomy and control. The Program was established with the justification for the government to improve the quality of Public Education. That is due to Elementary and Middle School nine years of schooling, having teachers to teach six-year-old children to read and write within two years, according to Federal Laws 11.114/05 and 11.274/06. The dissertation presents a brief panorama of the educational policies and State reform, created during Fernando Henrique Cardozo s administration as a possible solution for the critical situation of the State. What was intended was the decentralization of education in order to have civil society responsible for educational policies (devolution), accruing to State the control, coordination and financing of policies. Giving education a people s responsibility nuance, a quasi-market administration logic is created. A large-scale evaluation process becomes the landmark of educational policies, establishing, thus, efficiency and efficacy criteria for an improvement in management conduct standards. These, in turn, affected classroom practice as well as teachers identity. The introduction of non-reflexive training techniques based on competence should also be accounted for in the process of teacher training. The research adopts a qualitative approach assumption which involves the analysis of official documents and semistructured interviews with teachers, supervisors and principals of the schools that participate in the Alfa and Beto Reading and Writing Program. The collected data was analyzed using Bernstein and Ball as theoretical framework and using content analysis theoretical criteria that allows comprehending policies not just as macro and structured policies written in legal deeds as state policies to be applied, but also as action policies, which are re-contextualized and constructed, according to different contexts, by the subjects and actors involved in school practices. The findings demonstrate how teachers feel insecure, robotized, anxious, and controlled when submitted to programs lacking clarity on how to deal with teaching students, on how books exert control and deprive teachers of their autonomy. It also indicates the authoritarian way through which state public schools had to adopt Alfa & Beto programs and how teachers were accounted for the success or failure of the reading and writing process.